Pengolahan dan Pemanfaatan Sampah Rumah Tangga di Lingkungan Desa Tanjung Baru Kecamatan Indralaya Utara Kabupaten Ogan Ilir - Kurniawan, Rudy; Varbi S, Vieronica; Lionardo, Andries; Yusnaini, Yusnaini; Adam, Ryan (Jurnal Pengabdian Masyarakat Nusantara (JPMN), 2024)
The waste problem in Tanjung Baru Village is not a disaster if waste management is managed properly. Good waste management must of course have good environmental management wisdom as well. Environmental wisdom can be seen from how humans treat; objects, plants, animals, and anything around them. This is what is then called ecological intelligence, namely how a person's understanding and knowledge are in understanding their environmental ecosystem, so that they can care about the environment they live in. Therefore, the village asked the PKM team of the Faculty of Social and Political Sciences, Sriwijaya University to provide some kind of guidance to the people of Tanjung Baru Village in utilizing household waste. The low level of public understanding regarding the utilization of household waste causes household waste to be simply thrown away. Household waste processing that has not received the touch of processing technology. This can be seen from the absence of households that process household waste into useful processed products. Efforts to transfer information on household waste processing and utilization technology through this PkM activity have resulted in increasing the motivation and attraction of the community to carry out an environmental care movement by processing and utilizing the household waste produced. The people of Tanjung Baru Village have started to select organic and non-organic waste. Organic waste such as vegetables and leaves are processed into organic fertilizer, while leftover food is given to pets such as chickens and ducks. For non-organic waste, it is collected and sold to collectors of used goods and some are reused for home decorations, for example plastic bottles used as a medium for planting vegetables.